Carbapenem Resistance Of Pseudomonas Aeruginosa: A Review - Shaista Bakhat; Yasmeen Taj; Faisal Hanif (Journal of Bahria University Medical and Dental College)
Carbapenem resistance towards the gram negative microorganisms especially Pseudomonas aeruginosa is alarming and on-going public health problem all over the world. It may be intrinsic or acquired through transcription of genes among microorganisms. These genes are spreading rapidly and are responsible for serious out-breaks. So selection of antibiotics is limited to treat these resistant cases. Resistant genes are commonly extended in Europe, Asia (Turkey, India, China, Pakistan and so on) and South America. In Pakistan carbapenem resistance in Pseudomonas aeruginosa isolates is increasing among hospitalized patients. It shows a progressive trend in multidrug resistance (even towards last resort drug carbapenem). In this article, we offer an in-depth review of carbapenem resistant Pseudomonas aeruginosa. This will facilitate the readers to take effective measures in order to control infection and appropriate use of antibiotics.